Energy Sustainability and Pope Francis’ Encyclical on Care for our Common Home: National Policies and Corporations as Change Agents - Arogyaswamy, Bernard (Consilience, 2017)
It has been widely accepted by policy makers, corporate executives, and citizens alike that economic growth is the measure of a nation’s prosperity and well-being. The almost single-minded focus on growth, however, is achieved at high ecological and social cost, which has become a source of great concern. One of the driving forces behind unbridled growth has been the unquenchable thirst for energy worldwide. This paper investigates the challenges posed by the growth-energy nexus. While renewables are making giant strides, they account for a mere fraction of the world’s energy demand. The Papal Encyclical Laudato Si’ offers a detailed analysis of the harm humanity has inflicted on its common home, and the arguments developed in this paper are evaluated through the prism of the Encyclical. The underlying mindset preventing more sustainable ways of generating and using energy is explored, and the need to articulate human spirituality while accepting scientific consensus is emphasized. The recent international accord addressing climate change, already facing the threat of withdrawal by the United States after the recent election, can only work if the “technocratic” paradigm is radically modified. The paper provides evidence that national and local policies mirror public attitudes to tackle deteriorating environmental and social conditions. It concludes that corporations, mentioned in passing in the Encyclical, are beginning to play a central role in finding sustainable solutions, regardless of whether the international consensus holds.